Systematic review of interventions in the childcare setting with direct parental involvement: effectiveness on child weight status and energy balance-related behaviours - I. van de Kolk; S. R. B. Verjans-Janssen; J. S. Gubbels; S. P. J. Kremers; S. M. P. L. Gerards (BMC, 2019)
Abstract Background The early years are a crucial period to promote healthy energy balance-related behaviours in children and prevent overweight and obesity. The childcare setting is important for health-promoting interventions. Increasingly, attention has been paid to parental involvement in childcare-based interventions. The aim of this systematic review is to evaluate the effectiveness of these interventions with direct parental involvement on the children's weight status and behavioural outcomes. Methods A systematic search was conducted in four electronic databases to include studies up until January 2019. Studies written in English, describing results on relevant outcomes (weight status, physical activity, sedentary behaviour and/or nutrition-related behaviour) of childcare-based interventions with direct parental involvement were included. Studies not adopting a pre-post-test design or reporting on pilot studies were excluded. To improve comparability, effect sizes (Cohen's d) were calculated. Information on different types of environment targeted (e.g., social, physical, political and economic) was extracted in order to narratively examine potential working principles of effective interventions. Results A total of 22 studies, describing 17 different interventions, were included. With regard to the intervention group, 61.1% found some favourable results on weight status, 73.3% on physical activity, 88.9% on sedentary behaviour, and all on nutrition-related behaviour. There were studies that also showed unfavourable results. Only a small number of studies was able to show significant differences between the intervention and control group (22.2% weight status, 60.0% physical activity, 66.6% sedentary behaviour, 76.9% nutrition behaviour). Effect sizes, if available, were predominantly small to moderate, with some exceptions with large effect sizes. The interventions predominantly targeted the socio-cultural and physical environments in both the childcare and home settings. Including changes in the political environment in the intervention and a higher level of intensity of parental involvement appeared to positively impact intervention effectiveness. Conclusion Childcare-based interventions with direct parental involvement show promising effects on the children's energy balance-related behaviours. However, evidence on effectiveness is limited, particularly for weight-related outcomes. Better understanding of how to reach and involve parents may be essential for strengthening intervention effectiveness.